Development of Web-Based Geography Learning Media for High School Students - Rachmawati, Evita; Kurniawan, Bagus; Arkew, Habtu Worku; Singh, Archana (Journal Evaluation in Education (JEE), 2024)
Purpose of the study: This research aims to address the low student learning outcomes and motivation in the geography learning subjects of students at higher schools by developing and evaluating a web-based geography learning media using Moodle and examining its effectiveness in enhancing student learning achievement and interest. Methodology: This research uses an R&D method development procedure with six steps. The research subjects are 21 students in higher school. The data collection technique is a test using a before-after experimental design. Main Findings: The research data shows that Moodle's web-based geography learning media is effective and suitable. The validation by subject matter experts in geography shows that the learning media material is very good quality, with an average score of 92.5%. The media validation results show that the learning media is very good and suitable for application in the learning process, with an average score of 66.2%. The test results using a before-after experimental design show that the learning media can improve student learning outcomes with a significant difference of 5.570 ≥ 2.086, exceeding the expected outcome of 75%. Novelty/Originality of this study: Develop and evaluate a web-based geography learning media using Moodle for the geography learning subjects of higher school, which may have different characteristics and needs from other students in other regions or countries. The research has implications for improving the geography curriculum and the teacher training program in higher schools.